Revisiting the Quiet-Life Hypothesis in the Banking Sector: Do CEOs’ Personalities Matter? - Le TDQ; Nguyen DT; Ngo T (MDPI (Basel, Switzerland), 2024)
This study investigates the relationship between market power and bank profitability, and the impacts of CEOs’ personality traits, in Vietnam from 2007 to 2020. The analysis of CEOs’ signatures is used to determine their characteristics. The findings support the quiet-life hypothesis, which suggests that the negative relationship between market power and bank profitability may depend on CEOs’ characteristics. More specifically, the results show that conscientious CEOs with market power tend to reduce bank profitability, and this effect is more pronounced for foreign-owned banks. Therefore, our findings have critical implications for bank management.
Keywords: quiet-life hypothesis; chief executive officer (CEO); personalities; Vietnamese banks; profitability; generalized method of moments (GMM)